Effect of temperature on moisture sorption phenomena in agricultural products - Jiří Štencl (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2005)
The paper demonstrates importance of temperature influence on dehydration processes using drying model equations in introductory part and further presents results of water sorption tests of parsley leaves. Measurements were carried out under laboratory conditions in the temperature range of 10–40 °C and relative air humidity from 30 to 100%. Moisture sorption isotherms were tested using a gravimetric dynamic method with continuous recording of changes in sample weight. Five mathematical models available in the literature (Chung-Pfost, GAB, Halsey, Henderson, and Oswin) were statistical evaluated. The Henderson equation was found to be a good model both for moisture adsorption and desorption. Part of the sorption isotherms measured in parsley leaves show the type II BET classification shape. An increase in temperature causes an increase in water activity for the same moisture content and, if water activity is kept constant, an increase in temperature causes a decrease in the amount of absorbed water.